2008
DOI: 10.1097/ta.0b013e31816c5c80
|View full text |Cite
|
Sign up to set email alerts
|

Damage Control Hematology: The Impact of a Trauma Exsanguination Protocol on Survival and Blood Product Utilization

Abstract: We have demonstrated that an exsanguination protocol, delivered in an aggressive and predefined manner, significantly reduces the odds of mortality as well as overall blood product consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
296
0
7

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 357 publications
(307 citation statements)
references
References 24 publications
4
296
0
7
Order By: Relevance
“…Consequently, hemostatic function is compromised and different approaches have been explored to restore coagulation function. In the United States, blood products, such as platelet concentrates, cryoprecipitate, or fresh frozen plasma have been used in patients with bleeding complications (3,4). To observe the effects of fibrinogen on survival, Stinger et al performed a retrospective analysis in massive transfused trauma patients at a United States Army combat support hospital and reported that the amount of fibrinogen administered from transfused blood products correlates with survival (5).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, hemostatic function is compromised and different approaches have been explored to restore coagulation function. In the United States, blood products, such as platelet concentrates, cryoprecipitate, or fresh frozen plasma have been used in patients with bleeding complications (3,4). To observe the effects of fibrinogen on survival, Stinger et al performed a retrospective analysis in massive transfused trauma patients at a United States Army combat support hospital and reported that the amount of fibrinogen administered from transfused blood products correlates with survival (5).…”
Section: Introductionmentioning
confidence: 99%
“…These results, and the biologically plausible concept of treating haemorrhage with component ratios approaching those of whole blood, have led to the development of guidelines recommending early empirical use of FFP in traumatic bleeding [20]. Introducing massive transfusion protocols with increased ratios of FFP:PRBC has been shown to improve survival when compared with historical controls [21], but these findings are yet to be confirmed in a randomised trial.…”
Section: Haemostatic Resuscitationmentioning
confidence: 97%
“…This supports the anecdotal observation that generalized visceral edema is reduced when plasma and blood products are delivered via a crystalloid sparing MTP. 1,15,17 To this end, 4 patients with grade 4 trauma even underwent immediate fascial closure during the initial operative procedure. This compares to a mean wait of 4.2 days in the remaining patients who had successful approximation of their abdominal wall during the initial hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] While the effect on overall mortality in the civilian population is still debated, [21][22][23][24] massive resuscitations with high plasma:packed red blood cell (RBC) ratios remain promising for addressing the early coagulopathy 25 and acidosis frequently associated with life-threatening injury. 10 Additional benefits of a formal MTP include earlier administration of blood products during the resuscitation phase, improved overall efficiency, decreased total blood product use during a patient's hospital stay and a substantial economic savings.…”
mentioning
confidence: 99%
See 1 more Smart Citation